2004
DOI: 10.1136/gut.2003.035857
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of adenocarcinoma arising from the right side of the gastric cardia in NW Iran

Abstract: Background: In the West, the subsite incidence of gastric cancer has changed in recent decades, with cancer of the cardia increasing in incidence and that of the more distal stomach decreasing. NW Iran has a very high incidence of upper gastrointestinal cancer and we have examined the anatomical site specific incidence in this geographical region. Method and materials: Of 33 718 patients who visited our clinic from March 2000 to Jan 2003, 3119 (9.3%) with persistent upper gastrointestinal symptoms underwent up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Two studies [25,26] in particular have attracted our attention. It has been reported that the localization of dysplasia in BE and cardiac cancer is dominant at the 12 o'clock and 3 o'clock wall of the lower esophagus [25,26] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Two studies [25,26] in particular have attracted our attention. It has been reported that the localization of dysplasia in BE and cardiac cancer is dominant at the 12 o'clock and 3 o'clock wall of the lower esophagus [25,26] .…”
Section: Figurementioning
confidence: 99%
“…It has been reported that the localization of dysplasia in BE and cardiac cancer is dominant at the 12 o'clock and 3 o'clock wall of the lower esophagus [25,26] . However, we did not detect any corroborative findings in histological examinations in this study, thus more epidemiological studies will be required to examine this issue further.…”
Section: Figurementioning
confidence: 99%
“…GCC has become a significant cause of mortality and morbidity both in the west (3)(4)(5) and in Asia (6,7), especially in China (8). Although this cancer has become an important health problem worldwide, the its pathogenesis has not been well characterized (1).…”
mentioning
confidence: 99%
“…Iran with a high incidence of GC ranks fourth in Asia, after China, Japan and Korea respectively (Fujisawa et al, 1999;Wang and Wang, 2003;Derakhshan et al, 2004;Yim et al, 2007;Alizadeh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%